MMP24 Contributes to Neuropathic Pain in an FTO-Dependent Manner in the Spinal Cord Neurons - Ma, Longfei; Huang, Yangyuxin; Zhang, Fengjiang; Gao, Dave Schwinn; Sun, Na; Ren, Jinxuan; Xia, Suyun; Li, Jia; Peng, Xinyi; Yu, Lina; Jiang, Bao-Chun; Yan, Min (Frontiers in Pharmacology, 2021)
Nerve injury-induced gene expression change in the spinal cord is critical for neuropathic pain genesis. RNA N6-methyladenosine (m6A) modification represents an additional layer of gene regulation. We show that spinal nerve ligation (SNL) upregulated the expression of matrix metallopeptidase 24 (MMP24) protein, but not Mmp24 mRNA, in the spinal cord neurons. Blocking the spinal MMP24 increase attenuated the SNL-induced spinal neuronal sensitization and neuropathic pain development and maintenance. Conversely, mimicking this increase promoted the spinal ERK activation and produced evoked nociceptive hypersensitivity. Methylated RNA Immunoprecipitation Sequencing (MeRIP-seq) and RNA-immunoprecipitation (RIP) assay indicated the decreased m6A enrichment in the Mmp24 mRNA under neuropathic pain condition. Moreover, fat-mass and obesity-associated proteins (FTO) was colocalized with MMP24 in neurons and increased its binding to the Mmp24 mRNA in the spinal cord after SNL. Overexpression or suppression of FTO correlates with promotion or inhibition of MMP24 expression in cultured spinal cord neurons. In conclusion, SNL promoted the binding of FTO to the Mmp24 mRNA to erase the m6A level in the Mmp24 mRNA, and subsequently facilitated the translation of MMP24 in the spinal cord, which ultimately contributes to neuropathic pain.